A phenothiazine/dimesitylborane hybrid material as a bipolar transport host of red phosphor. Issue 40 (29th September 2016) - Cheng, Yu-Jen; Yu, Siao-Yin; Lin, Song-Cheng; Lin, Jiann T.; Chen, Li-Yin; Hsiu, Dai-Sin; Wen, Yuh Sheng; Lee, Mandy M.; Sun, Shih-Sheng
Abstract : High performance OLEDs with red-emitting phosphorescent iridium complexes doped in new bipolar transporters containing a meta -conjugated phenothiazine/dimesitylborane hybrid have been developed. Abstract : New bipolar transport compounds containing a meta -conjugated phenothiazine/dimesitylborane hybrid have been synthesized and three of them were characterized via single crystal structural determination. The compounds exhibited emission from blue to green, and one of them has a dual emission behavior. Organic light-emitting diodes using the compounds as the host for the red-emitting guest, Ir(pq)2 (acac) (bis(2-phenylquinoline)(acetylacetonate)iridium), have external quantum efficiencies in the range of 6.3–15.5%. Some devices have a negligible efficiency roll-off up to 1000 cd m −2 .